Clock without hand - McCullers, Carson 1917-1967 (Houghton Mifflin, 1998)
On the eve of court-ordered integration" in small-town Georgia, four characters interact: "J.T. Malone, a lonely, dying middle-aged druggist looking to redeem his misspent life; Fox Clane, a corrupt old judge and defender of the ways of the Old South; Jester Clane, the judge's orphaned grandson, a directionless adolescent with a strong sense of social justice; and Sherman Pew, an angry, blue-eyed black youth in search of his own identity."--Cover